Evaluation of a civic engagement approach to catalyze built environment change and promote healthy eating and physical activity among rural residents: a cluster (community) randomized controlled trial. - Seguin-Fowler, Rebecca A.; Hanson, Karla L.; Villarreal, Deyaun.; Rethorst, Chad D.; Ayine, Priscilla.; Folta, Sara C.; Maddock, Jay E.; Patterson, Megan S.; Marshall, Grace A.; Volpe, Leah C.; Eldridge, Galen D.; Kershaw, Meghan.; Luong, Vi.; Wang, Hua.; Kenkel, Don. (Tufts University. Tisch Library., 2022)
Keywords: Civic engagement, Built environment, Nutrition, Physical activity, Rural health equity, Social influence.; Springer Open.